Den geologiska utvecklingen av Hamrångesynklinalens suprakrustalbergarter, centrala Sverige - Erlandsson,Maria (Examensarbeten i geologi vid Lunds universitet, 2007)
The studied area is located in the western part of the Hamrånge syncline. In this area, the rocks, contacts and structures were mapped . Thinsections were investigated regarding petrography and microstructures, and representative thinsections were pointcounted. Three samples were selected for Rietveld analysis to receive the chemical compositions. Minerals from both the syncline and the area outside has been dated by the 40Ar/39Ar method. The Hamrånge area is located in the central part of Sweden, 30 km north of Gävle, near the Baltic coast. The Hamrånge syncline is mainly composed of well preserved supracrustal rocks belonging to the Svecofennian Domain. The supracrustal rocks are of both sedimentary and volcanic orgins. The later ranges from mafic to felsic in composition. In the studied area only volcanic rocks compose the bedrock. The volcanic sequence is a felsic volcanic rock occurring in the stratigrafically lowest parts, which are overlain by minor amounts of felsic-intermediate volcanic rock. Overlaying these rocks are mafic volcanics, dominated by mafic lavas, which is in turn overlain by maficintermediate volcanics. Between these rocktypes and in the felsic-intermediate volcanics are minor units of mineralised rocks. It is likely that felsic-intermediate volcanic rocks are stratigrafically on top of the mafic-intermediate volcanic rocks. The occurrence of redeposition of some volcanics and pillow lavas indicate a marine environment. Mainly the mafic lavas are occasionally altered to skarn. The central part of Svecofennium has been deformed by at least two major fold and thrust episodes related to D2 and D3. A previous deformation event, D1, has been recognised in metasedimentary rocks north of the Hamrånge syncline. The area has also been affected by later brittle deformation. Indications of an early deformation, D1, have been found at one locality in the Hamrånge area. This fabric can be related to either compaction or to tectonic deformation. Intense D2 deformation appears as a penetrative foliation and a strong stretching lineation. Both isoclinal F2 folds and D2 thrusts have been identified. F3 folds have been identified both as a regional fold and as minor open parasite folds. The F3 fold has a steep axial plane striking E-W and a fold axis plunging c. 23° to the east. The cooling history shows that the Hamrånge syncline and the highgrade area outside passed through the 350º isograde at about 1.74 Ga. Both the timing and the temperature when the two curves meet suggest that deformation occurred under semi-brittle conditions. One candidate is a deformation zone located south of the Hamrånge syncline.
Keywords: Svekofennium; Hamrångesynklinalen; 40Ar/39Ar; Rietveldanalys; strukturell anlys; petrografi; Svecofennium; Hamrånge syncline; Rietveldanalysis; structural analysis; petrography